2020
DOI: 10.1186/s40337-020-00320-5
|View full text |Cite
|
Sign up to set email alerts
|

“I’m not a teenager, I’m 22. Why can’t I snap out of it?”: a qualitative exploration of seeking help for a first-episode eating disorder during emerging adulthood

Abstract: Background: Eating disorders (EDs) typically have their onset during adolescence or the transition to adulthood. Emerging adulthood (~18-25 years) is a developmental phase which conceptually overlaps with adolescence but also has unique characteristics (e.g. increased independence). Emerging adults tend to come to ED services later in illness than adolescents, and emerging adulthood's unique characteristics may contribute to such delays. Objective: This study aimed to explore attitudes towards ED symptoms, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
0
14
0
3
Order By: Relevance
“…As symptoms become more compulsive and/or start to impact functioning, they are gradually reappraised. However, often stereotypical beliefs about EDs (e.g., EDs are characterised by extreme low weight; EDs are 'teenage' illnesses) delay help-seeking further (Potterton, et al, 2020). In a related study, FREED patients presenting to adult ED services (age 18-25) were directly compared to those presenting to Child and Adolescent ED services (below age 18).…”
Section: Discussionmentioning
confidence: 99%
“…As symptoms become more compulsive and/or start to impact functioning, they are gradually reappraised. However, often stereotypical beliefs about EDs (e.g., EDs are characterised by extreme low weight; EDs are 'teenage' illnesses) delay help-seeking further (Potterton, et al, 2020). In a related study, FREED patients presenting to adult ED services (age 18-25) were directly compared to those presenting to Child and Adolescent ED services (below age 18).…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that some participants perceived that early intervention, as delivered here, was “not early enough” for them, because they already had had symptoms for some time prior to specialist referral. This is perhaps not surprising, given the evidence that emerging adults tend to come to services with a longer duration of ED than other groups [ 11 , 12 , 42 , 43 ]. However, this finding further highlights that efforts to increase early help-seeking will be key to maximise the effectiveness of early intervention [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that this is a particularly pertinent concern during emerging adulthood, given that this life-stage is characterised by ongoing autonomy development and an “in-between” (childhood / adulthood) level of independence [ 48 , 49 ]. Indeed, asserting self-reliance and independence from caregivers has been previously highlighted as a particular concern for emerging adults with EDs [ 9 , 10 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that these concerns are related, with depression and anxiety mediating the relationship between sleep disturbance and EDs in college women (Goel et al., 2020). Furthermore, concerns about treatment—and in particular the potential involvement of parents—have recently been cited as a barrier to help seeking in emerging adults (Potterton, Austin, Allen, Lawrence, & Schmidt, 2020). Finally, university students with an ED reported that the illness hindered their ability to focus on academic responsibilities (Goldschen et al., 2019), and interference with life roles (e.g., ability to focus on studies) has been found to be a facilitator of help‐seeking in emerging adults (Potterton et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the PSYCHLOPS could be used to uncover possible sources of fear/obstacles to motivation to engage in treatment. This is particularly relevant as ED patients typically experience their symptoms as egosyntonic (Vitousek, Watson, & Wilson, 1998), especially in the early stages of illness (Potterton et al., 2020) and are ambivalent about receiving help (Leavey, Vallianatou, Johnson‐Sabine, Rae, & Gunputh, 2011). Additionally, the treatment concerns revealed by the PSYCHLOPS may also provide information helpful in collaboratively choosing between which type of evidence‐based therapy may be best suited to a patient.…”
Section: Discussionmentioning
confidence: 99%